UPAYA PENGEMBALIAN KERUGIAN NEGARA AKIBAT KORUPSI PENYALAHGUNAAN ALIH FUNGSI HUTAN - Presyta Nurhalida Putri Sejati, (Fakultas Hukum Universitas Trunojoyo Madura, 2023)
Corruption of forest function conversion is a form of corruption that not only harms the state, but can threaten the country's economic stability and even hinder the development of the country's economy as carried out by Surya Darmadi's PT Darmex Group Company which has illegally converted 37,095 hectares of forest area for oil palm plantations in Riau from 2003 to 2022, which resulted in the state suffering a loss of Rp.39.7 Trillion Rupiah. This research uses normative legal research by analyzing the case in Decision 62/Pid.Sus-Tpk/2022/Pn.Jkt.Pst, so that the approaches used are conceptual approaches, statue, and cases supported by primary, secondary and tertiary legal materials in this study. The results of this study indicate that verdict No. 62/Pid.Sus-Tpk/2022/Pn.Jkt.Pst has harmed justice in society considering the fantastic losses caused. The eradication of corruption is not only focused on punishing the perpetrators, but also focuses on returning state losses in accordance with the nominal (assets) that have been corrupted. Thus, asset recovery efforts in corruption cases are very important, the Indonesian government should follow up the national legislative process of the Draft Asset Forfeiture Law as a form of the government's seriousness in efforts to eradicate corruption in Indonesia.